Implementasi Pendidikan Multikultural Dalam Membentuk Karakter Toleransi Siswa - Sulistiyani, Sulistiyani (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Indonesia is a country that has diverse cultures, customs, races, tribes, ethnicities, religions and many more. This diversity is framed in the motto Bhineka Tunggal Ika which means